1,25-Dihydroxyvitamin D3-Conditioned CD11c+ Dendritic Cells are Effective Initiators of CNS Autoimmune Disease - Besusso, Dario; Saul, Louise; Leech, Melanie D.; O’Connor, Richard A.; MacDonald, Andrew S.; Anderton, Stephen M.; Mellanby, Richard J. (Frontiers in Immunology, 2015)
Dendritic cells (DC) play a crucial role in regulating T cell activation. Due to their capacity to shape the immune response, tolerogenic DC have been used to treat autoimmune diseases. In this study, we examined whether 1,25 dihydroxyvitamin D3-conditioned bone marrow-derived DC (VitD-BMDC) were able to limit the development of autoimmune pathology in experimental autoimmune encephalomyelitis (EAE). We found that VitD-BMDC had lower expression of MHC class II and co-stimulatory molecules and were less effective at priming autoreactive T cells in vitro. Using our recently described BMDC-driven model of EAE, we demonstrated that VitD-BMDC had a significantly reduced ability to initiate EAE. We found that the impaired ability of VitD-BMDC to initiate EAE was not due to T cell tolerization. Instead, we discovered that the addition of 1,25(OH)2D3 to BMDC cultures resulted in a significant reduction in the proportion of CD11c+ cells. Purified CD11c+ VitD-BMDC were significantly less effective at priming T cells in vitro yet were similarly capable of initiating EAE as vehicle-treated CD11c+ BMDC. This study demonstrates that in vitro assays of DC function can be a poor predictor of in vivo behavior and that CD11c+ VitD-BMDC are highly effective initiators of an autopathogenic T cell response.